KEBANGKITAN LADANG BERPINDAH DI NAGARI SILAYANG KECAMATAN MAPATTUNGGUL SELATAN KABUPATEN PASAMAN PROVINSI SUMATERA BARAT - Yusran, Juli; Yonariza, Yonariza; Elfindri, Elfindri; Mahdi, Mahdi (SOCA: Jurnal Sosial Ekonomi Pertanian, 2020)
Infrastructure development and ProRLK (deforested Land Rehabilitation Project) a Government of Indonesia collaboration prpject with The German Technical Coorperation Agency (GTZ) in 1992, has shifted the pattern of shifting cultivation to rubber farming in Nagari Silayang. Households engaged in shifting cultivation for food needs, stopped this entrenched practice, and focused on rubber plantations for food needs and financial means. But in recent years, the practice of shifting cultivation has been rife in Nagari Silayang. This phenomenon refutes the theory of agricultural transformastion in many previous studies, which concluded that shifting agricultural patterns lead to patterns that increasingly leave shifting cultivation. The purpose of this study, is to find the factors that cause farm households in Nagari Silayang to return to shifting cultivation, and find ways or strategies to stop forest clearing for swidden land. The research method used is descriptive qualitative and quantitative. Data collection uses observation, key informant interviews and household surveys. the results showed that the revival of shifting cultivation in Nagari Silayang was caused by the decline in global rubber prices, maintaining food security, and efforts to increase household income. This will have an impact on biodiversity damage and even natural disasters, because old forests are converted to agricultural land. This leads to negative impacts on biodiversity and can result in natural disasters, as old forests are converted to agricultural land.